Contribution of metals in resuspended dust to indoor and personal inhalation exposures: Relationships between PM10 and settled dust. (1st October 2018) - Rasmussen, Pat E.; Levesque, Christine; Chénier, Marc; Gardner, H. David
Abstract: This study investigated relationships between element concentrations in settled indoor dust and airborne particulate matter (PM), and characterized element concentrations in fine (PM2.5 ) and coarse (PM10-2.5 ) modes of indoor, outdoor and personal microenvironments. Concentrations in settled house dust correlated significantly (99% CI) with concentrations in indoor PM10 for 11 out of 17 studied elements: Ag, Al, As, B, Cu, Fe, Mn, Pb, U, V and Zn. Five elements showed significant correlations between personal PM10 and settled dust, at 99% CI for Ag, Al, and As; and at 95% CI for Mn and Sb. These significant dust- PM10 correlations were observed in non-smokers' homes in Windsor, Canada, in which PM10-2.5 comprised 55% of personal and indoor PM10 (median values in 2005 and 2006 respectively). Several elements were more concentrated in indoor PM10 compared to the settled dust from which the PM10 was derived, with enrichment factors ranging from 1.3 to 11. Dust fractionation experiments confirmed that most trace elements were enriched in resuspended PM10 compared to the parent dust sample. The <10 μm fraction averaged 50% ± 3.6% (by weight) of the total <80 μm dust samples (range 37–56%; n = 69). Concentrations of many elements in the <10 μm fraction of settled dust were 1.4–2.0 times higher in samples from heavily carpeted homes compared to non-carpeted homes, including Al, As and the transition metals Cd, Cr, Cu, Fe Ni and Zn. The results demonstrate that settled dust concentration data are useful for estimating indoor and personal exposures via the inhalation pathway. Highlights: Metals in resuspended house dust significantly influence the metal composition of indoor air PM. Correlations between personal PM10 and settled house dust are significant for several elements. Many elements are enriched in the inhalable fraction (<10 μm) of settled dust. Metal enrichment in inhalable particles is greater in dust from heavily carpeted homes. Indoor sources of metals can be significant even when indoor/outdoor ratios do not exceed unity.